Evaluation of genetic variation in Perilla for agro-morphological and quality traits - ANSARI, M A; PANDEY, AVINASH; KUMAR, SUDHIR; KUMAR, AMIT; M, SANGEETA; MEITEI, CH BUNGBUNGCHA; SHARMA, S K; ROY, S S; DAS, ANUP; MISHRA, D; SINGH, I M; PRAKASH, N (The Indian Journal of Agricultural Sciences, 2019)
Perilla is an important underutilized oilseed crop cultivated by tribal farmers in hilly areas of north-eastern region of India. It is grown by tribal and marginalised farmers in the traditional form of agriculture. The crop has good oil quality and plays an important role in providing nutritional security to the tribal farmers. There is a need to evaluate the traditional landraces grown by tribal farmers for studying the important traits which can help develop high yielding variety with quality traits. For this purpose, 29 Perilla genotypes were evaluated to assess the genetic variation. Wide spectrum of variability was observed for all 16 characters. The genotypic variance was moderate to high for the characters resulting in high heritability and moderate to high genetic advance values. Seed yield per plant positively correlated with all the traits except days to 50% flowering, leaf width, petiole length and seed oil content. The Perillagenotypes were grouped into seven distinct clusters. An analysis of the percentage contribution of individual characters towards genetic diversity revealed that seed yield per plant, Mn content and Cu content were the major characters contributing to genetic diversity in Perilla. Based on the results it is concluded that Perilla genotypes exhibit a widerange of variability for most of the traits. Some genotypes possessed desirable genes for more than one character and hence could be utilized directly or included in hybridization programme.